“Of rose and pomegarnet the redolent pryncesse”: Fashioning Princess Mary in 1525 - Hamrick, Stephen (Renaissance and Reformation / Renaissance et Réforme, 2017)
While a more accurate appraisal of Mary Tudor’s life and reign is underway, historians of literature continue either to ignore or to misinterpret surviving representations of Princess Mary. To begin correcting this failure, the article analyzes a complex 1525 verse portrait of Mary, setting that text within its contemporary political contexts. Analysis of William Newman’s unpublished manuscript poem, “My ladie princesse doughter to king harry the VIII,” recovers an intriguing characterization of the first Tudor princess in the period immediately prior to Henry’s divorce from Catherine of Aragon and frustrates attempts to understand the first Tudor queen as a lifelong loser destined to failure by her own limited abilities. Newman’s long poem represents the princess as uniquely qualified and admirably prepared to rule England as Henry’s heir.